Price variability of pembrolizumab across U.S. National Cancer Institute–designated Cancer Centers (NCICCs) from 2016-2021. Issue 28 (1st October 2022) - Hussaini, S. M. Qasim; Johnson, Jordan; Chino, Fumiko
Abstract : 48 Background: NCICCs are poorly compliant to price transparency rules set forth by the CMS. Competitive price shopping is prevented due to a lack of uniform rate setting, and service charges are often higher than what a hospital reasonably expects to be reimbursed. We investigated variability in the charged and reimbursed payments for pembrolizumab utilizing Medicare claims across all NCICCs. Methods: Medicare claims data from 2016-2021 for pembrolizumab (HCPCS J9271) infusions in a hospital outpatient department were selected from the Definitive Healthcare claims database for all hematology-oncology and medical oncology providers at NCICCs. Average charges, reimbursements, and total claims were obtained. Annual percentage changes (APC) were calculated to evaluate trends during study period. Prices are presented as inflation adjusted numbers (charged and reimbursed; 2021 dollars). Analyses were performed in Excel (Microsoft Corp). Results: Our analysis included 53 NCICCs of which 47 were part of the 340B Drug Pricing Program (NCI-340B), 11 were Prospective Payment System-exempt (NCI-PPS), and 6 NCICCs were both (PPS/340B). From 2016 to 2021, total Medicare claims increased from 9461 to 46291 across NCICCs, with NCI-PPS centers comprising 30% of claims. Total payments to NCICCs increased from 55.9M to 388.1M annually. Average charge for pembrolizumab in 2021 were: 45, 227 (NCI-PPS), 46, 000 (all NCICCs), 49, 057 (NCI-340B), 59, 392 (dual-eligible PPS/340B). During study period, APC were: 9.2% (NCICCs), 9.6% (NCI-340B), 12.8% (NCI-PPS), and 17.5% (dual-eligible PPS/340B). Despite high charged prices, reimbursement was much lower, about 18.4% (or 7364) of charged price at NCICCs over study period. Highest reimbursement was noted at NCI-PPS (22%, or 8551), and lowest at NCI-340B (16.4% or 7086) over study period. When considering a smaller cohort of PPS-only or 340B-only, PPS-only status was associated with lowest charged price but highest reimbursement (33.5%, or 8568). Conclusions: NCICCs charged > 4 times the average reimbursed price for pembrolizumab, with charges increasing faster than inflation. While lower charges were noted at NCI-PPS, they received higher reimbursement. Dual PPS/340B status commanded the highest charged prices and quickest price increases. Our study informs greater price transparency regulation at NCICCs and raises questions regarding utility of special status benefits from the federal government.2016-2021 NCICC trends. Center (n) Average Charges, /thousands, (2016-2021 range) Reimbursed % APC Total Claims Total Reimbursed Amount, /millions NCI (53) 40.1 (29.8-46.0) 18 9.2 183, 444 1, 353 NCI-PPS (11) 37.2 (24.7-45.2) 23 12.8 56, 972 488 NCI-340B (47) 43.1 (31.3-49) 16 9.6 137, 990 979 PPS-340B (6) 49.3 (27.3-59.3) 17 17.5 28, 006 239 PPS-only (4) 25.5 (21.0-30.0) 34 7.7 28, 996 248 340B-only (40) 38.9 (29.2-44.9) 16 9.44 105, 671 664